Cascading Effects of Major Natural Hazards in Greece - Michail-Christos Tsoutsos (Proceedings)
When a disaster occurs, society at risk is not only threatened by the consequences of this event. Stable and trigger factors generate a natural hazard, which in turn induces changes in some trigger factors, and thereby, these changes can induce another natural hazard. Furthermore, natural hazards are characterized by interactions, which consist of various types, such as triggering (cascading) interrelations. The purpose of this research is to identify, through a review process, the cascading effects of major natural hazards that occurred in Greece and had a significant impact on society.